Information structure in lesser-described languages studies in prosody and syntax - Adamou, Evangelia; Haude, Katharina; Vanhove, Martine (Studies in language companion series (SLCS),, 2018)
"The articles compiled in this volume offer new insights into the wealth of prosodic and syntactic phenomena involved in the encoding of information structure categories. They present data from languages which are rarely, if ever, taken into account in the most prominent approaches in information structure theory, and which belong to the Afroasiatic, Amerindian, Australian, Caucasian, and Niger-Congo language stocks. In addition to the significant descriptive value of these pioneering contributions, several studies also draw attention to previously undescribed or typologically rare phenomena. By adapting a variety of methods to under-described and endangered languages, ranging from experimental to naturalistic corpus studies, this volume also aims to serve as an invitation for further research in this direction"--